Phase II trial of neoadjuvant pemetrexed plus cisplatin followed by surgery and radiation in the treatment of pleural mesothelioma - Rea Federico; Adolfo Favaretto; Giuseppe Marulli; Lorenzo Spaggiari; DePas Tommaso Martino; Ceribelli Anna; Adriano Paccagnella; Gino Crivellari; Russo Francesca; Matteo Ceccarelli; Kazeem Gbenga; Marchi Paolo; et al. (2013)
Malignant pleural mesothelioma is an aggressive tumor that has a poor prognosis and is resistant to unimodal approaches. Multimodal treatment has provided encouraging results.Phase II, open-label study of the combination of chemotherapy (pemetrexed 500 mg/m²+cisplatin 75 mg/m² IV every 21 days × 3 cycles), followed by surgery (en-bloc extrapleural pneumonectomy, 3-8 weeks after chemotherapy) and hemithoracic radiation (total radiation beam 54 Gy, received 4-8 weeks post-surgery). The primary endpoint was event-free survival, defined as the time from enrollment to time of first observation of disease progression, death due to any cause, or early treatment discontinuation.Fifty-four treatment-naïve patients with T1-3 N0-2 malignant pleural mesothelioma were enrolled, 52 (96.3%) completed chemotherapy, 45 (83.3%) underwent surgery, 22 (40.7%) completed the whole treatment including 90-day post-radiation follow-up. The median event-free survival was 6.9 months (95%CI: 5.0-10.5), median overall survival was 15.5 months (95%CI 11.0-NA) while median time-to-tumor response was 4.8 months (95%CI: 2.5-8.0). Eighteen (33.3%) and 13 (24.1%) patients were still event-free after 1 and 2 years, respectively. The most common treatment-emergent adverse events were nausea (63.0%), anemia (51.9%) and hypertension (42.6%).Following two cardiopulmonary radiation-related deaths the protocol was amended (21 [38.9%] patients were already enrolled in the study): the total radiation beam was reduced from 54 Gy to 50.4 Gy and a more accurate selection of patients was recommended.The combination of pemetrexed plus cisplatin followed by surgery and hemithoracic radiation is feasible and has a manageable toxicity profile in carefully selected patients. It may be worthy of further investigation.Clinicaltrial.com registrationID #NCT00087698.